Penampungan Air dan Pengendalian Sarang Nyamuk dengan 3M - Muhammad Farid; Aidil Onasis; Erdi Nur; Asep Irfan; Muchsin Riviwanto (Poltekkes Kemenkes Padang, 2025)
The risk of dengue haemorrhagic fever transmission is influenced by several factors, including water storage facilities (TPA) and 3M behaviour. The city of Padang has the highest CFR for dengue haemorrhagic fever cases, at 0.76%. Vector control efforts are needed, including monitoring larvae in water storage facilities and implementing 3M, so that the chain of dengue haemorrhagic fever vector transmission can be broken. The purpose of this study is to determine the significance of the relationship between the number of WSS and 3M behaviour with larval density in Air Tawar Timur Village, Padang Utara District, Padang City, in 2025 so that it can become a. This study used an observational method with a cross-sectional approach. The study was conducted from January to June 2025 with a sample size of 86 houses. Data collection was conducted through observation using a mosquito larva density observation sheet with the visual larva method and interviews using a questionnaire. Data analysis was performed using univariate and bivariate analysis with Pearson's correlation test. From the 86 respondent households, there were 4.3 TPA and a standard deviation of 3.4 TPA. The 3M behaviour had an average of 36.5 and a standard deviation of 15.7, while the average larval density was 1.6 TPA with a standard deviation of 2.3 TPA. There is a relationship between the number of TPA and Larva Density in Air Tawar Timur Village, Padang City with p = 0.005. There is a relationship between 3M and Larva Density in Air Tawar Timur Village, Padang City with p = 0.015. It is concluded that there is a significant relationship between the number of landfills and 3M behaviour and larval density.